Assembly and phylogenetic analysis of complete chloroplast genome of a wild tobacco Nicotiana Attenuata - Haifeng Lin; Di Bai (Mitochondrial DNA. Part B. Resources, 2017)
Nicotiana attenuata (N. attenuata) is an annual herb that induces nicotine, volatiles and phenolics in response to damage. In this study, we assembled the complete chloroplast (cp) genome of N. attenuata with the length of 155,886 bp, which was composed of a large single copy region (LSC) of 86,602 bp, a small copy (SSC) region of 18,518 bp and a pair of inverted repeats (IR) of 25,383 bp. This typical cp genome contains 112 unique genes, including 78 protein-coding genes, 30 tRNA genes and four rRNA genes. Phylogenetic analysis of 32 plant cp genomes based on 76 conserved protein-coding genes shows that N. attenuata is evolutionarily close to N. tabacum, then Capsicum annuum. The complete cp genome sequence of N. attenuata may provide a crucial foundation for the study of evolution, molecular biology and genetic engineering in Nicotiana species.